2011
DOI: 10.1186/1471-2172-12-24
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Heat Shock Protein 70 in Health, Aging and Disease

Abstract: BackgroundHeat shock proteins (Hsp) are ubiquitously synthesised in virtually all species and it is hypothesised that they might have beneficial health effects. Recent studies have identified circulating Hsp as an important mediator in inflammation - the effects of low-grade inflammation in the aging process are overwhelming. While much is known about intracellular Hsp70, scant data exist on circulating Hsp70 in the aging context. Therefore, the objectives of this study were to investigate the effect of age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 47 publications
2
48
0
2
Order By: Relevance
“…Additionally, two-to four-fold increases in plasma levels of inflammatory mediators occur during the aging process, yet the association between serum HSP70 and age is unknown. A study in communitydwelling elderly people found that the serum concentration of HSP70 decreased with age in a normal population, with higher levels of HSP70 being associated with inflammation and frailty in elderly patients (Njemini et al 2011a). Furthermore, healthy elderly individuals might have proinflammatory profiles that downregulate inducible HSP70 (Marotta et al 2007).…”
Section: Detection Methods For Hsp70mentioning
confidence: 97%
“…Additionally, two-to four-fold increases in plasma levels of inflammatory mediators occur during the aging process, yet the association between serum HSP70 and age is unknown. A study in communitydwelling elderly people found that the serum concentration of HSP70 decreased with age in a normal population, with higher levels of HSP70 being associated with inflammation and frailty in elderly patients (Njemini et al 2011a). Furthermore, healthy elderly individuals might have proinflammatory profiles that downregulate inducible HSP70 (Marotta et al 2007).…”
Section: Detection Methods For Hsp70mentioning
confidence: 97%
“…It was assumed that this allele is linked to the C dominant allele of HSPA1B (-179C/T) and the CC genotype, which were associated with lower HSPA1A and HSPA1B mRNA levels and affected HSP70 production. Furthermore, HSP70 amount in human serum decreased with age in the normal population and inflammatory pathologies in elderly individuals were associated with elevated HSP70 levels [16]. However, it is currently unknown whether there is an association of polymorphisms in HSPs genes with the mechanisms which are important for the development and progression of the CMI.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was reported that mRNA expression levels for HSP70 in aged T lymphocytes [20] . It was found in a study they conducted on humans in various age groups that HSP70 level diminished depending on aging [21] . In another study, they conducted on young (5 months old) and old (24 months old) male Winstar rats that HSP70 expression was decreased in the shin and lung cells after a heat stres exposure [22] .…”
Section: Discussionmentioning
confidence: 99%